Readymade Boomerang : The Eighth Biennale of Sydney : Print Portfolio and Documentation. - Block, René; Kirker, Anne; Sartorius, Joachim; Daadgalerie, Berlin (Berlin : Daadgalerie Berlin, 1992)
Adams, Dennis ; Ben ; Bloom, Barbara ; Brehmer, Klaus-Peter ; Burchill, Janet ; Cage, John ; Cragg, Tony (Anthony) ; Gascoigne, Rosalie ; Hamilton, Richard ; Kabakov, Ilya ; Kaprow, Allan ; Norgaard, Bjorn ; Paik, Nam June ; Sarkis ; Schnabel, Julian ; Trockel, Rosemarie ; Tyndall, Peter ; Unsworth, Ken ; Webb, Boyd ; Weiner, Lawrence ; Williams, Emmett
biog., statements p. 98-107
Duits
Engels
The Readymade Boomerang, The Eighth Biennale of Sydney : Print Portfolio and Documentation, Daadgalerie Berlin, 1992
boek
Keywords: Sydney